A protease‐responsive fluorescent probe for sensitive imaging of legumain activity in living tumor cells. (16th May 2019) - Li, Xi; Liu, Qingzhu; Ye, Siqin; Wang, Shijie; Li, Ke; Lv, Gaochao; Peng, Ying; Qiu, Ling; Lin, Jianguo
Abstract: Legumain, a lysosomal cysteine protease, is critical for pathological progression and has been found to play an important role in the occurrence and development of several cancers. However, its biological functions remain few recognized. To further understand the role of legumain activity in tumor progression, a legumain protease‐responsive fluorescent probe was developed in the present study. The probe1 was synthesized by conjugating an aminoluciferin fluorophore with an alanine–alanine–asparagine (AAN) peptide sequence. The successful synthesis of probe1 was validated by NMR and MS spectra as well as HPLC analysis. The probe1 was non‐toxic and exhibited great stability in the physiological solutions. More importantly, compared with the aminoluciferin fluorophore, the peptide conjugation may dramatically increase the targeting specificity. Probe1 was able to effectively detect the legumain activity in living HCT116 cells through fluorescence imaging. All these results implied that probe1 could act as a promising fluorescent probe specialized for the monitoring of legumain activity in living cells. Abstract : A legumain protease‐responsive fluorescent probe was designed and synthesized by conjugation of an aminoluciferin fluorophore with the alanine–alanine–asparagine (AAN) peptide sequence. The probe can be selectively activated by the legumain‐overexpressing HCT116 cell lysates and showed strong fluorescence in the HCT116 cells. The probe showed promising value for sensitive detection of legumain‐overexpressing cancer cells.